Development of acute chest pain services in the UK. Issue 2 (24th January 2007) - Cross, Elizabeth; How, Steven; Goodacre, Steve
Abstract : Background: In 2001, a survey of emergency departments in the UK showed wide variation in the management of acute undifferentiated chest pain. There has since been substantial development of chest pain services and research into chest pain units (CPUs). Aim: To determine whether practice had changed in 2006. Methods: All emergency departments in the UK were surveyed by postal questionnaire to the lead clinician or first named consultant. Results: Responses were received from 192 of 253 (76%) departments. 25 (10%) stated they had a CPU, although 8 (32%) of these were set up in trials. Many CPUs provided care that was similar to that provided by hospitals without a CPU, with 76% using 10–12 h troponin and 29% only providing delayed access to exercise tolerance testing (up to 2–3 weeks after attendance). Over all departments, the proportion with access to exercise testing had more than doubled between 2001 and 2006, from 21% to 49% (94/190), although only a minority (16%) were able to provide this immediately or within the next working day. Use of departmental guidelines for patients with chest pain had increased from 42% to 72% of departments. Use of troponins increased from 52% to 96%, whereas use of creatine kinase MB decreased from 54% to 31% of departments. Availability of short-stay facilities had more than doubled from 21% to 59%. Conclusions: Formal development of CPUs has been limited and mostly restricted to trials. However, there has been substantial informal and ad hoc development of acute chest pain services. Development of chest pain services in the UK is progressing in a disorganised way.